Acquisition of agricultural real estate for public purpose investments - Wojciechowski, Paweł (Przegląd Prawa Rolnego, 2024)
The aim of the article is to present the impact of the instruments restricting the trade in agricultural real estate introduced in the Act on shaping the agricultural system on the implementation of public purpose investments, and to evaluate, in particular in the context of the proportionality principle, the solutions adopted. To this end, the author has pointed out that the statutory regulations based on the casuistic method are not appropriate, inconsistent and raising many doubts; and has therefore proposed a solution which would uniformly, by virtue of the law itself, exclude restrictions on the acquisition of agricultural real estate for the purpose of realising public purpose investments, but would nevertheless preserve the instruments of supervision of this trade.